Impact of risk-taking culture on financial recovery from the East Asian Financial Crisis. - Goh, Li Ying. (2008)
The main aim of this paper was to investigate how different risk-taking cultures affect local banks' recovery from the EAFC in 1997-1998. In addition, the study hoped to suggest appropriate risk-taking behaviour that is better suited to aid the local banking sector during times of crises.